Learning Portuguese, constructing identity: a single-case study of a Pakistani student in Brazil - Camila Quevedo Oppelt (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada)
ABSTRACT Due to growing interest in less common languages, Portuguese as an additional language has seen a rise in popularity, particularly in academic settings. Despite this, research on foreign graduate students learning Portuguese in Brazil remains scarce. This study investigates the cultural and identity (re)construction of one such student. Grounded in Vygotsky’s (1978) theory and informed by the Sociocultural Theory of Second Language Development (Lantolf, 2013) and investment theory developed by Bonny Norton (1995), which emphasize identity and motivation, we explore the experiences of a foreign graduate student at a southern Brazilian public university. Our analysis reveals a complex interplay between language development and cultural integration, ultimately suggesting the participant achieved his academic and professional goals - including successful completion of Portuguese courses - through language proficiency. By recollecting Abdul’s Muslim identity, it becomes clearer how social identities are constructed and reconstructed in and from social interactions. This highlights the limitations of simplistic views about learning - they are far more intricate than we often realize. The interplay between social interactions, power dynamics, and language development becomes clear: these elements are fundamentally linked.